Interspecies Signaling and Habituated Conviviality - Hendlin, Yogi (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2018)
The conviviality of sharing habitat can lead species to learn and benefit from other species’ signals, even if those communications are not intended for them. Purposeful interspecific signaling is also common. Forms of symbiotic semiosis, intentional and unintentional, result from repeated interactions between cohabitating species. Attunement to neighboring species’ dispositions through sharing habitat carves overlapping grooves in the semiosphere predictable for organisms to make some sense of their overlapping Umwelten. Interspecies semiosis may be less generalizable than conspecific signaling, yet these interactions nonetheless can be interpreted as a form of modus vivendi ethics.